Comparing the efficacy of three techniques to reduce isoagglutinin titers in AB0 incompatible kidney transplant recipients. (November 2017) - Parmentier, S.P.; Rosenkranz, E.; Schirutschke, H.; Opgenoorth, M.; Quick, C.; Hoelig, K.; Rosner, A.; Hohenstein, B.; Hugo, C.; Passauer, J.
Abstract: ABO incompatible (ABOi) organ transplantation requires pre-transplant reduction of the recipient's IgG and IgM isoagglutinin titer against the donor to prevent hyperacute rejection. Over the past four years we primarily used unspecific IgG immunoadsorption (IA) for this purpose and combined this selectively with membrane filtration (IAc) to reduce IgM isoagglutinines. In patients with an initial IgG titer against donor below 1:64, plasma exchange (PE) was initiated. In this retrospective analysis covering January 2012 to August 2015 we compared how efficiently IgG and IgM isoagglutinines in a total of 22 ABOi kidney transplant recipients were reduced by either IA (n = 75 sessions), IAc (n = 14 sessions) or PE (n = 40 sessions). Median pre-treatment IgG isoagglutinin titers were 32 (4–4096) while IgM titers were 16 (1–256) respectively. Mean IgG reduction by either treatment modality was 1.3 ± 0.9 (IA), 1.8 ± 1.0 (IAc) and 2.6 ± 1.3 (PE) titer steps per session (p < 0.001 IA vs. PE; p < 0.04 PE vs. IAc). Mean IgM reduction was 0.6 ± 0.6 (IA), 1.8 ± 0.8 (IAc) and 2.4 ± 1.9 (PE) titer steps (p < 0.001 for both IA vs. PE and IA vs. IAc). Our data indicate that PE efficiently removed IgG- and IgM isoagglutinines. By processing only half the plasma volume per treatment PE was twice as effective as IA in terms of IgG-type isoagglutinin removal in our patient group. This is best explained by the presence of soluble AB0 antigens in the FFP used as plasma replacement. These advantages in efficacy have to be weighed against the potential hazards of PE. Combination of IA and plasma filtration effectively removes IgM-type and even enhances net IgG-type isoagglutinin elimination compared to IA alone. When trying to avoid PE, combined application of IA and IAc is a possible and effective way to reduce isoagglutinin titers before ABOi transplantation.